(untitled) (Journal of Ideas in Health, 2024)
Background: Senile prostate enlargement is an age-related condition. Many sexually active patients fear formal prostate surgeries owing to their negative impact on sexual performance. Minimally invasive procedures, including prostate water vapor thermal therapy (Rezūm®), were devised to make ends meet. This study aims to present a comprehensive narrative synthesis about the impact of prostate water vapor therapy on sexual functions. Methods: A narrative literature review was performed in May 2023, using MEDLINE, Cochrane Library, Ovid-Embase, Scopus, Science Direct, and Google Scholar; for the MeSH term “rezum AND sexual functions”. Selected reports were published articles from 2018 to date (the last 5 years). Only open-access journals in English were analyzed. Efforts were made to focus on the 2 main domains of sexual functions; erection and ejaculation. Results: As per the concise MeSH term “rezum AND sexual functions”, a score of 207 hits appeared on the initial search. After eliminating duplicate and irrelevant papers, only 7 articles fulfilled the inclusion criteria and were subjected to analysis. The analyzed articles were critically appraised to point out the studies` strengths and limitations. The gathered data were found to be consistent with one another as no outliers were detected. Conclusion: Water vapor thermal therapy of the prostate showed satisfying preservation of erectile function with minimal ejaculatory dysfunction.